2020
DOI: 10.3390/insects11120863
|View full text |Cite
|
Sign up to set email alerts
|

Tick Preventive Behaviors and Practices Adopted by Medical Students from Poland, Germany, and Thailand in Relation to Socio-Demographic Conditions and Their Knowledge of Ticks and Tick-Borne Diseases

Abstract: Given the high medical importance of ticks, we analyzed the most common preventive behaviors and practices adopted by medical students from Poland, Germany, and Thailand, and the level of their knowledge of ticks and tick-borne diseases. A survey consisting of 19 questions was conducted among 636 randomly selected students. The study showed that the Polish and German students preferred inspection of the body on their return home (86.9% and 63.5%, respectively) and wearing protective clothes (79.8% and 32.3%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…Despite the above, few studies have been conducted and published on people's knowledge, attitude, and practices regarding tick and TBDs, with even fewer from Pakistan, where TBDs are causing devastating economic losses [50][51][52][53][54][55][56]. With this in mind, the current study was designed to evaluate livestock owner's knowledge, attitude, and practices towards ticks in Punjab, Pakistan, to assess the awareness about ticks and TBDs, zoonotic concerns, and need for a One Health approach towards tick control in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above, few studies have been conducted and published on people's knowledge, attitude, and practices regarding tick and TBDs, with even fewer from Pakistan, where TBDs are causing devastating economic losses [50][51][52][53][54][55][56]. With this in mind, the current study was designed to evaluate livestock owner's knowledge, attitude, and practices towards ticks in Punjab, Pakistan, to assess the awareness about ticks and TBDs, zoonotic concerns, and need for a One Health approach towards tick control in this region.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in France, a study identified the need for further training in serology limitations and the availability of TBE vaccination among primary care physicians [ 40 ]. Similarly, only 56.2% of students from Germany, Poland, and Thailand declared their knowledge of the risks posed by ticks and TBPs to be sufficient [ 41 ]. Another study from northeastern France underlined the importance of information on TBE among workers exposed to tick bites [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of tick-borne diseases is based on tick biology, ecology and control measures. Reducing tick abundance with the use of biological and chemical methods could be inefficient [12]. However, practices for tick bite prevention, knowledge and attitudes can reduce TBD risk for individuals, especially since research on a LB vaccine has still not been finalized.…”
Section: Discussionmentioning
confidence: 99%